CD28 Blockade Ex Vivo Induces Alloantigen-Specific Immune Tolerance but Preserves T-Cell Pathogen Reactivity - Dillinger, Barbara; Ahmadi-Erber, Sarah; Soukup, Klara; Halfmann, Angela; Schrom, Silke; Vanhove, Bernard; Steinberger, Peter; Geyeregger, Rene; Ladisch, Stephan; Dohnal, Alexander Michael (Frontiers in Immunology, 2017)
Donor T cells contribute to reconstitution of protective immunity after allogeneic hematopoietic stem cell transplantation but must acquire specific tolerance against recipient alloantigens to avoid life-threatening graft-versus-host disease (GvHD). Systemic immunosuppressive drugs may abrogate severe GvHD, but this also impedes memory responses to invading pathogens. Here we tested whether ex vivo blockade of CD28 co-stimulation can enable selective T cell tolerization to alloantigens by facilitating CD80/86-CTLA-4 signaling. Treatment of human allogeneic dendritic cell/T cell co-cultures with a human CD28 blocking antibody fragment (a-huCD28) significantly abrogated subsequent allospecific immune responses, seen by decreased T cell proliferation and of type 1 cytokine (IFN-γ and IL-2) expression. Allo-tolerization persisted after discontinuation of CD28 blockade and secondary alloantigen stimulation, as confirmed by enhanced CTLA-4 and PD-1 immune checkpoint signaling. However, the T cells retained reactivity to pathogens, supported by clonotyping of neo-primed and cross-reactive T cells specific for Candida albicans or third-party antigens using deep sequencing analysis. In an MHC-mismatched murine model we tolerized C57BL/6 T cells by ex vivo exposure to a murine single chain Fv specific for CD28 (a-muCD28). Infusion of these cells, after a-muCD28 washout, into bone marrow-transplanted BALB/c mice caused allo-tolerance and did not induce GvHD-associated hepatic pathology. We conclude that selective CD28 blockade ex vivo can allow the generation of stably allo-tolerized T cells that in turn do not induce graft-versus-host reactions while maintaining pathogen reactivity. Hence, CD28 co-stimulation blockade of donor T cells may be a useful therapeutic approach to support the immune system after HSCT.